Impact of green HRM practices on bank employee service behaviors - Md Sayed Uddin; Md. Atikur Rahaman; Wasib Bin LATIF; Priyanka Das Dona; Debashis Kundu (ResearchGate, 2023)
This study aims to examine the influence of green human resource management (HRM) practices on the service behaviors of bank employees operating in the banking sector of Bangladesh. The study endeavors to offer valuable insights into the effectiveness of green HRM practices in enhancing practices and employee service behaviors in the banking sector. The results indicate that green human resource management practices have a beneficial influence on employee service behaviors by green knowledge sharing, green training and development, green performance appraisal, green reward system. This study also emphasizes how green HRM practices affect banks in terms of organizational sustainability, employee motivation, talent acquisition and retention, and the necessity of ongoing evaluation and improvement. Moreover, the current study used convenience sampling techniques to collect data from 258 workers of several commercial banks in Bangladesh using a self-reported questionnaire that had been modified from other studies. 95% confidence interval was used to accept the hypotheses during regression analysis. The results show that each and every hypothesis is supported, whereas hypothesis tests were analyzed using SPSS version 26.0. The results show that employees’ knowledge sharing tendency, training facility, performance appraisal and reward system have a significant and positive impact on bank employees’ service behavior. This study may contribute to the growing subject of sustainable HRM and offers useful advice for banks looking to include environmental sustainability into their HRM plans to spur progress and enhance service.